Rescue transventricular off-pump mitral valve repair with artificial neochords for acute mitral regurgitation due to postinfarction papillary muscle rupturePerspectiveCentral Message - Mindaugas Budra, MD; Vilius Janušauskas, MD, PhD; Aleksejus Zorinas, MD, PhD; Diana Zakarkaitė, MD, PhD; Audrius Aidietis, MD, PhD; Robertas Samalavičius, MD, PhD; Kęstutis Ručinskas, MD, PhD (JTCVS Techniques)
Background: We report 3 cases of rescue transventricular off-pump mitral valve (MV) repair in high-risk patients with acute mitral regurgitation (MR) due to post–myocardial infarction (MI) papillary muscle rupture (PMR). Methods: The 3 patients presented with acute inferior ST elevation myocardial infarction, cardiogenic shock, and pulmonary edema. Their preoperative peak troponin I levels were 1909 ng/L, 16,963 ng/L, and 8299 ng/L. All 3 patients underwent successful percutaneous intervention to the culprit coronary artery, and antiplatelet therapy was initiated. All patients required inotropic support and had an intra-aortic balloon pump inserted preoperatively. Transesophageal echocardiography (TEE) demonstrated severe eccentric MR due to the leaflet prolapse secondary to PMR. The patients’ estimated EuroSCORE II scores were 16.03%, 16.68%, and 7.81%, and their Society of Thoracic Surgeons scores were 14.77%, 18.24%, and 9.8%, respectively. All 3 patients underwent urgent transventricular off-pump MV repair using artificial chords, with 2 or 3 three neochords implanted. The duration of operation was <2 hours, and intraoperative and postoperative drainage was minimal in all cases. MV function was assessed by qualitative and semiquantitative TEE. Results: Intraoperative MR reduction to a mild level was achieved in all 3 patients. All patients had moderate MR at discharge, likely due to left ventricular remodeling. Severe MR recurred in all patients, at 5, 4, and 2 months of follow-up, respectively. All 3 patients underwent an elective MV reoperation via conventional approach. Conclusions: Off-pump transventricular MV repair may offer a safe and feasible alternative to stabilize high-risk patients with acute MR due to post-MI PMR. Although early MR recurrence is concerning, urgent transventricular MV repair may serve as a bridge to conventional surgery in such unstable patients.